The politics and poetics of supppression and “memory loss”: the (re)construction of popular culture in post-Yugoslav Croatian discourse - Boris (Anafora, 2022)
The article discusses the role of subculture in Croatia and wider South Slavic context during and after the transitional period from the hegemony of Yugoslav communist system to the national state and its new narratives. The introduction discusses the modalities of memory loss in regard to the Yugoslav system of values. It focuses on the situation in popular culture and the new media, arguing that the process of memory loss has been orchestrated by the new national hegemony in both the media and politics and in the subcultural environment of marginal groups. The emphasis is put on the discursive tactics that have contributed to this process in the public sphere. The second part of the article concentrates on the relationship between the private and the public spheres and pays special attention to the relation between spontaneous subcultural practices and orchestrated mass-cultural outlets that very often construct the sphere of popular cultural needs. It is argued that the modalities of re-constructing and re-directing the narrative as an ethical (ethnic and political) issue remain an important topic not only for a better understanding of popular culture’s hegemonic order but also for the modalities of survival of the narrative as a literary autonomous field.